Possibilities of Farm Management Decision Support - Szilágyi, Róbert (Acta Agraria Debreceniensis, 2003)
Computer science has a major role in the decision-making process of farmers. In this process IT can be applied to virtually all phase: from infromation gathering to information processing. I am examining the position of informatics in the decision-making process. IT can be used in every single phases of the decision-making process. In my essay the useage of Internet and the possibilities it can provide play a significant role.After a brief description of the IT position of Hungarian agriculture I am introducing some programs, which can be used in the management’s decision-supporting system. Besides the Hungarian experiences the West European surveys also comfirm the application of Information Technology.